2010
DOI: 10.1038/ejcn.2010.97
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index and incident hypertension in rural women in China

Abstract: Background/Objectives: To evaluate the association between body mass index (BMI) and incident hypertension in a cohort of rural women in the Chinese population. Subjects/Methods: A population-based sample of 11 468 rural Chinese women aged X35 years and free from hypertension at baseline were followed-up from 2004-2006 to 2008. We calculated BMI from measured weight and height. Incident hypertension was defined as systolic blood pressure (BP) X140 mm Hg, diastolic BPX90 mm Hg or current use of antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…S1. We identified 56 prospective cohort studies , whose characteristics are presented in Table S2. One study reported results for two separate cohort studies and was regarded as two different studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1. We identified 56 prospective cohort studies , whose characteristics are presented in Table S2. One study reported results for two separate cohort studies and was regarded as two different studies .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 57 prospective cohort studies with 2,343,466 participants and 216,182 incident cases of HTN were included in meta‐analysis. Twenty studies were from the USA , 13 studies were from Europe , 20 studies were from Asia , 2 studies were from Africa , 1 study was from Mexico and 1 was from Brazil . Baseline characteristics of included studies are presented in Table S2, and reported risk estimates in relation to different categories of anthropometric measures in each study are presented in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have indicated that body mass index (BMI) is generally positively associated with blood pressure [6], which is also the case in China [7]. Overweight and obesity is an emerging epidemic in China, with almost 30% of the adult population being classified as either overweight or obese [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, little research has investigated people living in rural areas1011. Whether people with normal BMI but high WC or high BMI but normal WC would show increased risk of hypertension is unclear.…”
mentioning
confidence: 99%